Teachers’ Challenges and Job Performance under the Universal Basic Education Scheme in Rivers State, Nigeria (2007-2015) - Wilson, Goddey (Covenant University Journal of Politics and International Affairs, 2016)
The central focus of this paper is to identify the challenges teachers face in the course of discharging their basic responsibilities, and the impact of the challenges on the teachers’ job performance in Rivers State under the Universal Basic Education (UBE) scheme. The scope of the study is on the job activities and challenges of the teachers, the Rivers State Government’s role in the implementation process of the UBE objectives in the state, and the attendant consequences of the teachers’ job challenges on both the students and the state, within the period of 2007 and 2015. Expectancy-value is used as the theoretical framework of analysis to explain teachers’ job performance in the schools, secondary data are employed for the study and content analysis engaged as a tool to analyze the data. The study findings prove among other things, that poor motivation, manpower imbalance, political influence on teachers’ appointment and inadequate workshop and teaching facilities are teachers’ challenges while discharging their duties in the schools. The study further established that the teachers’ challenges have significant impact on the teachers’ job performance in the state UBE. Arising from the findings, some recommendations were made as strategies to reduce teachers’ challenges and improve on their job performance in the state UBE. Keywords : Challenges, Job Performance, Expectancy-value